Analisis Etika Bisnis Perang Diskon Antara Perusahaan Ritel dan UMKM Lokal - Rifqi Januariansyah; Halimah Zahrah; Jihan Az-Zahra Nurhaliza; Nanda Baihaqi; Faisal Taufiqurohman (Jejak digital: Jurnal Ilmiah Multidisiplin, 2025)
The growth of modern retail in Indonesia, especially through the Alfamart and Indomaret chains, has created a very dynamic competitive landscape. One prominent form of competition is the practice of discount wars and product exclusivity, which aims to win consumer loyalty and strengthen market dominance. This study aims to examine these practices from a business ethics perspective, with a particular focus on their impact on consumers and MSMEs in Bandung City. The method used is qualitative-descriptive research with a case study approach, through interviews with consumers and MSMEs, field observations, and literature studies from relevant sources. The results of the study show that although discount wars provide short-term benefits for consumers, this practice creates market dependency, reduces product diversity, and inhibits the growth of local MSMEs. Meanwhile, product exclusivity is considered to lead to hidden monopoly practices and limits consumer freedom of choice. From a business ethics perspective, both strategies have the potential to violate the principles of justice, social responsibility, and economic sustainability. Therefore, stricter regulations are needed from local governments and an ethical commitment from retail players in building a more inclusive and equitable market ecosystem.